Gas flow calibrations performed at the National Metrology Institute of South Africa (NMISA). (3rd November 2014) - Jonker, D.; Tarnow, E.P.
Abstract : The National Metrology Institute of South Africa (NMISA) Gas Flow Laboratory provides traceability to the South African Industry for gas flow measurements. A new primary standard for gas flow calibrations was purchased and commissioned. With three flow cells, a flow range of 0.5 mL/min to 50 000 mL/min is covered. The main features of this standard are accuracy, speed and convenience. This paper describes the activities of the NMISA Gas Flow Laboratory – a discussion of the primary standard, the validation thereof, calibration methods for client instrumentation, analysis of measurement results and the calculation of measurement uncertainties.